Estudio de Calidad de la Energía Implementando Filtros Activos para la Corrección de Armónicos (2011)
The Universidad Antonio Nariño – Tunja, is promoting studies about power quality to characterize the electrical signals, since industry in Boyaca has been growing in the last decades, and the mining sector has contributed to the progressive consumption of electrical energy using machines with powerful motors. This project is based on the study, analysis and approaching solutions of the problems caused by harmonic distortion, in the electrical utility of low voltage, existing in the stone crasher path of Socalito municipality Paz del Rio, due to present problems in power quality, and approaching a solution through active filters application. The study was carried out with the purpose of increasing efficiency, reliability and quality in the processes that are developed within the company; but also to reduce the environmental impact by reducing the harmonic components which are reflected mainly in the decrease in the consumption of electric power, mainly due to the reduced reactive power consumption, electromagnetic fields present in the plant, as well as possible physical effects that these have on the workers. The social impact associated is the awareness of the industries about the importance of controlling and operating their machines and processes reliably, safely end efficiently, without affecting the quality of production, increasing the competitiveness and taking best standards of industrial safety, especially reducing electric hazard. The economical impact will be justified with the no interruption of plant production which is associated to interruptions and predictive – corrective maintenance in the machinery; in the same way the cost reduction of the electric bill could be reduced by reducing the reactive power consumption.